Analysis Of The Influence Of Compensation And Training On The Performance Of Bpo Business Partner Outsourcing (BPO) Employees At The Development Bank Of Singapore Limited - Zaky, Achmad; Kusnadi, Kusnadi; Markonah, Markonah (Management Research Studies Journal, 2024)
Study This aim For analyze role Compensation and Training To BPO Employee Performance at The Development Bank of Singapore Limited . Study This using primary data and the data used in study This obtained from spread questionnaire to employee with BPO status at The Development Bank of Singapore Limited . Data on research This processed use SPSS application version 26. Population in study is employee with BPO status at The Development Bank of Singapore Limited as many as 40 respondents and methods taking sample is saturated sampling , so sample used​ as many as 40 respondents . Research result in a way Partial showing compensation influential significant to performance employee whereas training No influential to performance employees , and values coefficient The determination of R 2 is 0.381 which is significant that ability variables independent that is Compensation and Training in explain variable dependent namely Employee Performance as big as 38.1 % and the remaining 62.9 % are influenced by factors that are not​​ researched in research this , so recommended For study Next to add variable other independent factors such as : motivation , competence and so on . It is also recommended that it be improved compensation so that performance employee increase , Keywords: Compensation , Training , Employee Performance